2017
DOI: 10.1007/s00296-017-3860-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of coronary arteries in early rheumatoid arthritis prior to anti-rheumatic therapy

Abstract: Accelerated coronary atherosclerosis is common in patients with rheumatoid arthritis (RA). To examine coronary artery calcification (CAC) frequency and severity, its correlation with traditional risk factors (TRF) of cardiovascular diseases (CVD) and inflammatory markers in patients with early RA prior to anti-rheumatic therapy. RA adult patients (ACR/EULAR criteria, 2010, duration ≤ 12 months, without prior administration of disease-modifying anti-rheumatic drugs, glucocorticoids) underwent 32-row scanning fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
2
1
0
1
Order By: Relevance
“… 68 In another prospective study, coronary artery calcification (CAC) was detected in 46% of RA patients. 69 Other studies also reported similar findings. 72 , 90 In a prospective study by Wahlin et al , patients with RA who had CAC were found to have increased values of DAS28 and ESR, implying that inflammation plays a role in mediating RA-induced CAC.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“… 68 In another prospective study, coronary artery calcification (CAC) was detected in 46% of RA patients. 69 Other studies also reported similar findings. 72 , 90 In a prospective study by Wahlin et al , patients with RA who had CAC were found to have increased values of DAS28 and ESR, implying that inflammation plays a role in mediating RA-induced CAC.…”
Section: Discussionsupporting
confidence: 57%
“…68 In another prospective study, coronary artery calcification (CAC) was detected in 46% of RA patients. 69 Other studies also reported similar findings. 74 This study also reported that once RA patients developed CAC, the rate of progression was found to be similar to the progression seen in control participants.…”
Section: The Role Of Endothelial Dysfunctionsupporting
confidence: 57%
“…Повышение риска сердечно-сосудистых заболеваний (ССЗ) при СКВ может быть обусловлено как традиционными кардиоваскулярными факторами риска (ТФР), так и факторами, связанными с самим заболеванием (активностью болезни, ВН, присутствием aФЛ и использованием ГК) [139][140][141]. Формирование атеросклеротических бляшек в сосудах, кальцификация коронарных артерий, увеличение толщины комплекса интима-медиа (КИМ)ранние проявления поражения сердечно-сосудистой системы у больных СКВ [142,143].…”
Section: сердечно-сосудистые заболеванияunclassified
“…Recently, a meta-analysis demonstrated that RA patients exhibited increased coronary calcium scores [ 3 ]. Remarkably, RA is related with traditional CV risk factors [ 4 ], subclinical atherosclerosis [ 5 , 6 ], arrhythmias [ 7 ], and coronary calcifications [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%